Literature Review: Implementation of Extended Reality for Micro, Small, and Medium Enterprises in Indonesia - Handayani, Wiwik; Sihananto, Andreas Nugroho; Yulianto, Rusman (Jurnal Economia, 2025)
AbstractExtended Reality (XR), encompassing Virtual Reality (VR) and Augmented Reality (AR), constitutes immersive computer-generated technologies. While predominantly implemented in larger enterprises, XR adoption in Micro, Small, and Medium Enterprises (MSMEs) is notably sparse. XR's projected significance in product marketing, such as Meta Company and industry experts, this paper investigates XR adoption in Indonesian MSMEs from 2020 to 2023. Our review identifies ten instances of XR implementation in MSMEs, primarily in early developmental stages with limited user experience. The application of the (TAM) underscores the importance of user-centric evaluations in the adoption process. The balance between affordability, technological readiness, and consumer appeal will be key factors influencing the future dynamics of XR adoption in the business sector. Theoretical implications suggest a potential shift in marketing dynamics for MSMEs, while practical implications underscore the need for enhanced XR integration strategies to unlock the technology's full potential in empowering smaller enterprises.